Educational Management in Mosque-Based Institutions: A Case Study of the Baitul Muttaqin Islamic Center, East Kalimantan - Bahrani Bahrani; Arnani Arnani (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2025)
Mosque-based educational institutions play a vital role in supporting the academic, moral, and spiritual development of Muslim communities. Their effectiveness, however, depends on sound educational management practices. This study explores how the Baitul Muttaqin Mosque Islamic Center implements core management functions across its formal and non-formal educational units. A qualitative descriptive approach was employed, collecting data through in-depth interviews, participant observations, and document analysis with key informants, including the head of the Education and Training Unit (UPT), principals, teachers, and administrative staff. Data were analyzed using Miles, Huberman, and Saldaña’s interactive model, complemented by source and method triangulation to ensure credibility. Findings reveal that educational management is structured and value-driven but evolving. Planning is internally coordinated yet lacks consistent stakeholder participation. Organizational practices function effectively, although the absence of written job descriptions sometimes leads to role overlap. Program implementation integrates academic learning with Islamic values, but limited library resources and digital infrastructure constrain optimal delivery. Supervision is regular but informal, without standardized evaluation tools or independent review mechanisms. The study concludes that the Islamic Center demonstrates substantial progress in aligning Islamic educational values with contemporary management practices. Enhancing stakeholder engagement, formal documentation, resource provision, and supervision mechanisms will improve sustainability and effectiveness, positioning mosque-based educational institutions as models for integrated Islamic education in Indonesia.